KEDUDUKAN DAN TANGGUNG JAWAB HUKUM PIHAK SUB KONTRAKTOR PADA PERJANJIAN PENGADAAN BARANG/JASA PEMERINTAH - Mitha Miranda Sari (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2015)
Abstract: "Legal Status and Responsibilities of Sub Contractors Party on the Agreement Procurement of Government Goods / Services" analyze legal problems /issues namely, the Law considerations of the main contractors and sub-contractors to make sub contract procurement of goods / services of the government, the legal relationship between sub-contractors and main contractors with the government, the legal responsibilities of the sub-contractors in getting the default by the sub-contractor, the sub contractor procurement of government goods / services is not made as notarized ,there are differences in the regulation of sub-contract in Article 87 paragraph (3) of Presidential Regulation No. 70 of 2012 prohibited while Article 24 paragraph (1) of Law  The Act No. 18 year 1999 on Construction Services allow for the sub contract. The theory framework in this study consisted of Grand Theory: Theory of Equitable Legal Certainty, legal liability theory. Middle Range Theory: Theory of Public Contracts Characteristically (Publiekrechtelijk overeenkomst), the theory as a Notary Public Officials. Applied Theory: Principles consensual, the freedom to make contracts, strength of binding contracts, goodwill, balance, habits, indemnities, timeliness, force majeure, dispute resolution, the principle of the goods / services of the government. The Research methods using type hermeneutic research paradigm. The research approach using Normative Approach, Statue approach, legal Philosophy approach, conceptual approach, legal Historical approach, Sociolegal approach.. The technique of taking conclusions with Deductive method so that it is concluded that the legal considerations around contractors and sub contractors to make sub contract In Clause of Article 8 paragraph (1) in agreement with the main contractor the goods / services of the government, and special expertise for achievement, and the non-legal considerations is cost efficiency. Judgements are binding relationship and The Legal Responsibilities  to the main contractor and sub-contractors only, not to the government. It is suggested the agreement the sub-contract made as notarized by a notary public official authorized to guarantee legal certainty and fairness to the parties, so as not to violate Article 87 paragraph (3) Presidential Regulation No. 70 Year 2012 on Procurement of Government Goods/Services that the Deed made is the Partnership Act Consortium Agreement for Joint Operation (KSO) is set out in Chapter III Instruction to Participants Procurement (IKPP) in the Annex to Regulation Agency Chief Procurement Policy/government Services No. 6 of 2012 on the Technical Guidelines Presidential Regulation No. 70 Year 2012 on Procurement of Government Goods/Services. Keywords: Legal Status , Legal Responsibilities,Sub Contract, Procurement of Government Goods / Services